In vivo Evaluation of Essential Oils and Biocontrol Agents Combined with Hot Water Treatments on Carrot Seeds Against Alternaria radicina. Issue 2 (13th May 2015) - Lopez‐Reyes, Jorge Giovanny; Gilardi, Giovanna; Garibaldi, Angelo; Gullino, Maria Lodovica
Abstract: Seed‐dressing with essential oils from aromatic plants (savoury and thyme) and with antagonistic bacteria strains ( Pseudomonas spp.) was tested after a hot water treatment against Alternaria radicina inoculated on carrot seeds. Seed treatments by immersion in water at 55°C for 10 min improved the efficacy on pathogen control of the treatments with biocontrol agent strains more than the efficacy of those with essential oils. Pretreatment with hot water also increased the germination rate of carrot seeds. A mild phytotoxic effect was observed on the germination rate and the fresh biomass obtained from seeds treated with both essential oils. Treatments with essential oils and antagonistic bacteria presented positive results when combined with hot water dipping of seeds on control of A. radicina, but the effect was not completely additive. The formulation and the application method of the non‐chemical products tested are critical on their development as an alternative strategy on seed disinfection.